Penanganan Kasus Low Self-Esteem dalam Berinteraksi Sosial Melalui Konseling Rational Emotif Teknik Reframing - Maynawati, Aldila Fitri R.N. (Universitas Negeri Semarang, 2012)
Self-esteem is the most important thing for creating a good personality. Self-esteem is an individual evaluation from the differentiation between self-image and ideal-self. However, low self-esteem is often experienced by several individuals in sosial interaction which happened at SMP Negeri 2 Ungaran. The aim of this research is to know whether the case low self-esteem in social interaction of VIII grade students could be solved through rational emotive counseling by using reframing technique. This research used case handling approach. In addition, the method that used are interview and observation. In analising data, the researcher used comparative analysis, content analysis, and logic analysis. After giving treatment to three students, can be seen that students who had low self-esteem had changed with had rational beliefe, when meeting with his friends no longer beat the view, the intensity of the client alone in a classroom when recess was already reduced, it looks more confident when interact with his friends, and his was not ashamed and afraid when hanging out with friends. The research can be concluded that low self-esteem can be solved through rational emotive counseling by using reframing technique.